Accuracy of patient-specific implants in virtually planned segmental Le Fort I osteotomies - Kühle, Reinald; Scheurer, Mats; Bouffleur, Frederic; Fuchs, Jennifer; Engel, Michael; Hoffmann, Jürgen; Freudlsperger, Christian (Journal of Clinical Medicine, 2023)
(1) Background: In orthognathic surgery, segmental Le Fort I osteotomies are a valuable method to correct maxillary deformities or transversal discrepancies. However, these procedures are technically challenging, and osteosynthesis can be prone to error. (2) Methods: In this retrospective, monocentric cohort study, patients were enrolled who underwent a virtually planned segmental maxillary osteotomy during their combined treatment. Positioning and osteosynthesis were achieved by either a 3D-printed splint and conventional miniplates or patient-specific implants (PSI). The preoperative CT data, virtual planning data, and postoperative CBCT data were segmented. The deviation of all the segments from the desired virtually planned position was measured using the analysis function of IPS CaseDesigner. (3) Results: 28 Patients in the PSI Group and 22 in the conventional groups were included. The PSI group showed significantly lower deviation from the planned position anteroposteriorly (−0.63 ± 1.62 mm vs. −1.3 ± 2.54 mm) and craniocaudally (−1.39 ± 1.59 mm vs. −2.7 ± 3.1 mm). For rotational deviations, the pitch (0.64 ± 2.59° vs. 2.91 ± 4.08°), as well as the inward rotation of the lateral segments, was positively influenced by PSI. (4). Conclusions: The presented data show that patient-specific osteosynthesis significantly reduces deviations from the preoperative plan in virtually planned cases. Transversal expansions and vertical positioning can be addressed better.
Veröffentlicht: 18. September 2023
Gesehen am 24.10.2023